School canteen and the law: with special reference to Shah Alam / Nurfaida Mohd Rashidee and Syazwani Zawawi - Mohd Rashidee, Nurfaida; Zawawi, Syazwani (2008)
School canteens are said to play a vital role in producing and managing healthy food for students and school children. However, there are still no specific regulations that cover these matters. This research will focus on the needs to implement or to convert rules on school canteen guidelines into law in order to give more authoritative effect to ensure compliance. Apart from that, it will generally touch on the issue of food poisoning and hygiene with the suggested solution to overcome problems or to highlight the seriousness of this issue. It is also hoped that this research will increase knowledge and understanding on the issues regarding cleanliness and hygiene of the school canteen. It is aimed to discover a better solution on how to standardize the regulation in all school canteens in Malaysia to lead it to better management and to decrease the issues of food poisoning and the issue of hygiene to ensure the safety of the schoolchildren.